Notch‐inducing hydrogels reveal a perivascular switch of mesenchymal stem cell fate. (2nd July 2018) - Blache, Ulrich; Vallmajo‐Martin, Queralt; Horton, Edward R; Guerrero, Julien; Djonov, Valentin; Scherberich, Arnaud; Erler, Janine T; Martin, Ivan; Snedeker, Jess G; Milleret, Vincent; Ehrbar, Martin
Abstract: The fate of mesenchymal stem cells (MSCs) in the perivascular niche, as well as factors controlling their fate, is poorly understood. Here, we study MSCs in the perivascular microenvironment of endothelial capillaries by modifying a synthetic 3D biomimetic poly(ethylene glycol) (PEG)‐hydrogel system in vitro . We show that MSCs together with endothelial cells form micro‐capillary networks specifically in soft PEG hydrogels. Transcriptome analysis of human MSCs isolated from engineered capillaries shows a prominent switch in extracellular matrix (ECM) production. We demonstrate that the ECM phenotypic switch of MSCs can be recapitulated in the absence of endothelial cells by functionalizing PEG hydrogels with the Notch‐activator Jagged1. Moreover, transient culture of MSCs in Notch‐inducing microenvironments reveals the reversibility of this ECM switch. These findings provide insight into the perivascular commitment of MSCs by use of engineered niche‐mimicking synthetic hydrogels. Synopsis: Synthetic hydrogels serve as microenvironments for the formation of micro‐capillaries by endothelial cells and mesenchymal stem cells. Perivascular MSCs change phenotype and extracellular matrix, a reversible switch also induced in Jagged1‐modified hydrogels. MSCs support micro‐capillary formation of endothelial cells in synthetic PEG‐hydrogels. Micro‐capillary MSCs undergo perivascular commitment including an ECM switch. Notch‐inducing hydrogels induce the reversible ECM switch in MSCs in the absence of endothelial cells. Abstract : Synthetic hydrogels serve as microenvironments for the formation of micro‐capillaries by endothelial cells and mesenchymal stem cells. Perivascular MSCs change phenotype and extracellular matrix, a reversible switch also induced in Jagged1‐modified hydrogels.